Comparison of heart girth or flank-to-flank measurements for predicting sow weight - Iwasawa, T.; Young, M.G.; Keegan, T.P.; Tokach, Michael D.; Goodband, Robert D.; DeRouchey, Joel M.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
In previous Swine Day Reports we have demonstrated that feeding sows in gestation on the basis of body weight and backfat thickness is more precise and economical than methods of feeding based on visual observation of body-condition score. To simplify the weight and backfat procedure, we have estimated sow weight based on the correlation between heart girth (circumference of the sow measured behind the front legs) and weight. The objective of this study was to determine if a different sow measurement, flank to flank, would be as accurate as the heart-girth measurement. Sows were weighed and measured behind the front legs for heart girth or in front of the back legs for flank-to-flank measurement, and regression equations to estimate sow weight were developed. A total of 605 sows from three farms were used for the girth measurement. A total of 306 sows from two farms were used for the flank-to-flank measurement. The heart-girth equation was: weight, lb = 21.54 × heart girth, in – 684.76. The flank-to-flank measurement was: weight, lb = 26.85 × flank-to-flank, in – 627.93. The average residual was 30.8 lb for the heart girth measurement and 31.4 lb for the flank-to-flank measurement. Both of these measurements provide a reasonable weight estimate that can be used to determine weight categories for more accurately feeding gestating sows.
Keywords: Swine; Heart girth; Pigs; Prediction equations; Sows; Weight